Compound and method for producing same
By developing a new compound and adopting a specific reaction process, the problem of difficult material with high refractive index and excellent film-forming and curing properties in the prior art is solved, and efficient optical properties and stable curing properties are achieved.
Patent Information
- Application Number
- CN202380063239.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-24
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to provide materials with high refractive index, excellent film forming and curing properties for use in optical devices and display devices.
A new compound is developed, denoted as formula (I), and a compound with excellent properties and its cured substances are prepared by specific reaction steps such as reaction of formula (II) and formula (III), and reaction with a vulcanizing agent.
The cured substance with a high refractive index has excellent film forming and curing properties, and is suitable for the manufacturing of display devices and solid-state imaging devices.
Smart Images

Figure CN119816486A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a compound and a method for producing the same. In addition, the present invention also relates to a composition comprising the compound, a cured product of the compound or the composition, a display device comprising the cured product, and a solid-state imaging device comprising the cured product. In addition, the present invention relates to a sealing material and an insulating material comprising the composition. Background Art
[0002] In the field of optical devices, high refractive materials are eagerly desired. A lens can be obtained using a high refractive material, and a light path in an optical device can be controlled using the lens. In solid-state imaging devices, lenses are used for the purpose of improving the efficiency of focusing light into each photoelectric conversion element, and in display devices, lenses are used for the purpose of improving the efficiency of extracting light from pixels. In the past, various high refractive materials have been developed (for example, Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2011 / 102258 Summary of the invention
[0006] Problems to be solved by the invention
[0007] One object of the present invention is to provide a novel compound that can provide a cured product showing a high refractive index and has excellent film-forming properties and curing properties, and a method for producing the same. Another object of the present invention is to provide a composition comprising the compound, a cured product of the compound or the composition, a display device comprising the cured product, and a solid-state imaging device comprising the cured product.
[0008] Means for solving problems
[0009] The present invention includes the following contents.
[0010] [1] A compound represented by the formula (I).
[0011]
[0012] [In formula (I),
[0013] L represents a divalent group, and a plurality of L's may be the same or different.
[0014] m represents 0 or 1, and a plurality of m's may be the same or different.
[0015] A represents an O atom or a S atom, and plural A's may be the same or different.
[0016] n represents an arbitrary integer from 0 to 3, and a plurality of n may be the same or different.
[0017] R represents a monovalent substituent, and when there are plural Rs, the plural Rs may be the same or different.
[0018] R 2 represents a hydrogen atom or a monovalent substituent, and there are multiple R 2 Can be the same or different.
[0019] In formula (I), two groups represented by the following formulae are bonded to the 1-position and 6-position, the 2-position and 6-position, or the 2-position and 7-position of the naphthalene ring.
[0020] ]
[0021] [2] The compound according to [1], wherein all L are alkanediyl groups.
[0022] [3] The compound according to [1] or [2], wherein all m are 0.
[0023] [4] A composition comprising the compound according to any one of [1] to [3].
[0024] [5] The composition as described in [4], further comprising a polymerization initiator.
[0025] [6] The composition according to [5], wherein the polymerization initiator is a thermal cationic polymerization initiator or a thermal anionic polymerization initiator.
[0026] [7] The composition according to any one of [4] to [6], further comprising a polymerization inhibitor.
[0027] [8] A cured product of the compound according to any one of [1] to [3] or the composition according to any one of [4] to [7].
[0028] [9] A display device comprising the cured product described in [8].
[0029]
[10] A solid-state imaging device comprising the cured product described in [8].
[0030]
[11] A sealing material comprising the compound described in any one of [1] to [3] or the composition described in any one of [4] to [7].
[0031]
[12] An insulating material comprising the compound described in any one of [1] to [3] or the composition described in any one of [4] to [7].
[0032]
[13] The method for producing the compound according to any one of [1] to [3], which comprises the first step, or the first step and the second step.
[0033] Step 1: a step of reacting a compound represented by formula (II) with a compound represented by formula (III) to obtain a compound represented by formula (I) wherein A is an O atom;
[0034] Step 2: A step of obtaining a compound represented by the above formula (I) in which the above A is an S atom by reacting the compound represented by the above formula (I) in which the above A is an O atom with a sulfiding agent.
[0035]
[0036] [In formula (II), n and R have the same meanings as above.
[0037] The two -SH groups in formula (II) are bonded to the 1-position and 6-position, 2-position and 6-position, or 2-position and 7-position of the naphthalene ring.]
[0038]
[0039] [In formula (III), R 2 , L and m have the same meanings as above, and X represents a leaving group.]
[0040] Effects of the Invention
[0041] According to the present invention, it is possible to provide a new compound and a method for manufacturing the same which can supply a cured product that demonstrates a high refractive index and is also excellent in film forming property and curability. In addition, it is possible to provide a composition comprising the compound, a cured product of the compound or the composition, a display device comprising the cured product, and a solid-state imaging device comprising the cured product. In addition, according to the present invention, it is possible to provide a sealing material having a small linear thermal expansion coefficient and an insulating material having excellent dielectric constant and dielectric loss tangent. DETAILED DESCRIPTION
[0042] <Compound>
[0043] The compound of the present invention is a compound represented by formula (I) (hereinafter also referred to as "compound (I)"). Compound (I) can provide a cured product showing a high refractive index, and can also show excellent film-forming properties and curing properties. In addition, compound (I) can show excellent storage stability.
[0044]
[0045] [In formula (I),
[0046] L represents a divalent group, and a plurality of L's may be the same or different.
[0047] m represents 0 or 1, and a plurality of m's may be the same or different.
[0048] A represents an O atom or a S atom, and plural A's may be the same or different.
[0049] n represents an arbitrary integer from 0 to 3, and a plurality of n may be the same or different.
[0050] R represents a monovalent substituent, and when there are plural Rs, the plural Rs may be the same or different.
[0051] R 2 represents a hydrogen atom or a monovalent substituent, and there are multiple R 2 Can be the same or different.
[0052] In formula (I), two groups represented by the following formulae are bonded to the 1-position and 6-position, the 2-position and 6-position, or the 2-position and 7-position of the naphthalene ring.
[0053] ]
[0054] In formula (I), when there are multiple Rs, it means that at least one of them may be bonded to any position of the 1-4 positions of the naphthalene ring, and the rest may be bonded to any position of the 5-8 positions of the naphthalene ring. In addition, the multiple Rs may all be bonded to any position of the 1-4 positions of the naphthalene ring, or may all be bonded to any position of the 5-8 positions of the naphthalene ring. The same applies to the two Rs in the formulas (Ia-1), (Ia-2), (Ib-1), (Ib-2), (Ic-1), and (Ic-2) described later.
[0055] Examples of the two Ls representing a divalent group include, independently of one another, a divalent aliphatic chain hydrocarbon group which may have a substituent, a divalent alicyclic hydrocarbon group which may have a substituent, a divalent aromatic hydrocarbon group which may have a substituent, and a divalent group formed by a combination of these (such as an aralkylene group).
[0056] -CH2- in the divalent hydrocarbon group can be replaced by -O-, -S-, -NR 1A -(R 1A represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), -CO-, -SO2-.
[0057] As the divalent aliphatic chain hydrocarbon group, for example, a saturated or unsaturated aliphatic chain hydrocarbon group can be mentioned, and specifically, an alkane diyl such as methylene, ethylene, propane diyl, butane diyl, pentane diyl, hexane diyl, heptane diyl, octane diyl, nonane diyl, decane diyl, undecane diyl, dodecane diyl, tridecane diyl, tetradecane diyl, pentadecane diyl, hexadecane diyl, heptadecandiyl, octadecane diyl, nonadecandiyl, eicosane diyl, etc. can be mentioned. The divalent aliphatic chain hydrocarbon group can be straight chain or branched. The number of carbon atoms in the divalent aliphatic chain hydrocarbon group is usually 1 to 20, preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, and even more preferably 1 or 2.
[0058] Examples of the substituent which the divalent aliphatic chain hydrocarbon group may have include a halogen atom such as a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, a hydroxyl group, an amino group, an acetyl group, and a cyano group.
[0059] Examples of the divalent alicyclic hydrocarbon group include saturated or unsaturated alicyclic hydrocarbon groups, and specifically, monocyclic alicyclic hydrocarbon groups such as cyclopropanediyl, cyclobutanediyl, cyclopentanediyl, cyclohexanediyl, cyclooctanediyl, cyclononanediyl, and cyclodecanediyl; and polycyclic alicyclic hydrocarbon groups such as bicyclo[1.1.0]butanediyl, tricyclo[2.2.1.0]heptanediyl, bicyclo[3.2.1]octanediyl, bicyclo[2.2.2.]octanediyl, adamantanediyl, bicyclo[4.3.2]undecanediyl, and tricyclo[5.3.1.1]dodecanediyl. The number of carbon atoms in the divalent alicyclic hydrocarbon group is usually 3 to 20, preferably 3 to 10, more preferably 3 to 6, and even more preferably 5 or 6.
[0060] Examples of the substituent that the divalent alicyclic hydrocarbon group may have include alkyl groups having 1 to 10 carbon atoms (preferably 1 to 4 carbon atoms) such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl, halogen atoms such as fluorine, chlorine, bromine and iodine atoms, hydroxyl, amino, acetyl and cyano groups.
[0061] The divalent aromatic hydrocarbon group may be monocyclic or polycyclic, and examples thereof include phenylene, naphthylene, anthracenediyl, fluorenediyl, etc. The divalent aromatic hydrocarbon group usually has 6 to 20 carbon atoms, and preferably 6 to 10 carbon atoms.
[0062] Examples of the substituent that the divalent aromatic hydrocarbon group may have include alkyl groups having 1 to 10 carbon atoms (preferably 1 to 4 carbon atoms) such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl, halogen atoms such as fluorine, chlorine, bromine and iodine atoms, hydroxyl, amino, acetyl and cyano groups.
[0063] At least one of the two L's is preferably an alkanediyl group, and both are more preferably alkanediyl groups. In this case, the alkanediyl group preferably has 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms, further preferably 1 to 4 carbon atoms, and even more preferably 1 or 2 carbon atoms.
[0064] The two m's are each independently 0 or 1, and are preferably 0. More preferably, the two m's are both 0.
[0065] The two A's are each independently an O atom or a S atom, and preferably both are S atoms.
[0066] The two n are each independently any integer of 0 to 3, preferably any integer of 0 to 2, and more preferably 0 or 1. It is further preferred that both of the two n are 0.
[0067] When there are a plurality of Rs, R representing a monovalent substituent may be independently exemplified by monovalent hydrocarbon groups such as monovalent aliphatic chain hydrocarbon groups which may have a substituent, monovalent alicyclic hydrocarbon groups which may have a substituent, monovalent aromatic hydrocarbon groups which may have a substituent, and monovalent groups formed by combinations thereof (such as aralkyl groups); hydroxyl groups; amino groups, monomethylamino groups, monoethylamino groups, dimethylamino groups, diethylamino groups, methylethylamino groups, etc. which may be substituted by one or two groups. An amino group substituted with an alkyl group having 1 to 6 carbon atoms; a heterocyclic group such as an aliphatic heterocyclic group having 4 to 20 carbon atoms, such as pyrrolidinyl, pyrrolinyl, imidazolidinyl, imidazolinyl, oxazolinyl, thiazolyl, piperidinyl, morpholinyl, piperazinyl, indolyl, isoindolyl, quinolyl, thienyl, pyrrolyl, and furanyl, or an aromatic heterocyclic group having 3 to 20 carbon atoms; a halogen atom; a nitro group; a cyano group; a carboxyl group; a sulfone group; a thiol group; a formyl group; an -SF3 group; or an -SF5 group. -CH2- in a monovalent hydrocarbon group may be replaced by -O-, -S-, or -NR 1B -(R 1B represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), -CO-, -SO2-. It should be noted that as a group obtained by replacing -CH2- contained in a monovalent hydrocarbon group with -O-, there can be mentioned alkoxy groups having 1 to 12 carbon atoms such as methoxy, ethoxy, propoxy, butoxy, pentyloxy, hexyloxy, heptyloxy, octyloxy, and alkoxyalkyl groups such as methoxymethyl, ethoxymethyl, and methoxyethyl.
[0068] As the monovalent aliphatic chain hydrocarbon group, for example, a saturated or unsaturated aliphatic chain hydrocarbon group can be mentioned, and specifically, alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, etc. can be mentioned. The monovalent aliphatic chain hydrocarbon group can be straight-chain or branched. The number of carbon atoms in the monovalent aliphatic chain hydrocarbon group is usually 1 to 20, preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, and even more preferably 1 or 2.
[0069] Examples of the substituent which the monovalent aliphatic chain hydrocarbon group may have include a halogen atom such as a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, a hydroxyl group, an amino group, an acetyl group, and a cyano group.
[0070] Examples of the monovalent alicyclic hydrocarbon group include saturated or unsaturated alicyclic hydrocarbon groups, specifically, monocyclic alicyclic hydrocarbon groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclooctyl, cyclononyl, and cyclodecyl; and polycyclic alicyclic hydrocarbon groups such as bicyclo[1.1.0]butyl, tricyclo[2.2.1.0]heptyl, bicyclo[3.2.1]octyl, bicyclo[2.2.2.]octyl, adamantyl, bicyclo[4.3.2]undecyl, and tricyclo[5.3.1.1]dodecyl. The number of carbon atoms in the monovalent alicyclic hydrocarbon group is usually 3 to 20, preferably 3 to 10, more preferably 3 to 6, and even more preferably 5 or 6.
[0071] Examples of the substituent that the monovalent alicyclic hydrocarbon group may have include alkyl groups having 1 to 10 carbon atoms (preferably 1 to 4 carbon atoms) such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl, halogen atoms such as fluorine, chlorine, bromine and iodine atoms, hydroxyl, amino, acetyl and cyano groups.
[0072] The monovalent aromatic hydrocarbon group may be monocyclic or polycyclic, and examples thereof include phenyl, naphthyl, anthracenyl, fluorenyl, etc. The monovalent aromatic hydrocarbon group usually has 6 to 20 carbon atoms, and preferably 6 to 10 carbon atoms.
[0073] Examples of the substituent that the monovalent aromatic hydrocarbon group may have include alkyl groups having 1 to 10 carbon atoms (preferably 1 to 4 carbon atoms) such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl, halogen atoms such as fluorine, chlorine, bromine and iodine atoms, hydroxyl, amino, acetyl and cyano groups.
[0074] R 2 represents a hydrogen atom or a monovalent substituent, and there are multiple R 2They may be the same or different, but are preferably the same. Specific examples of the monovalent substituent include the same monovalent substituent as R. 2 Each independently is preferably a hydrogen atom or a monovalent aliphatic chain hydrocarbon group, more preferably a hydrogen atom or a monovalent aliphatic chain hydrocarbon group having 1 to 6 carbon atoms, further preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, particularly preferably a hydrogen atom, a methyl group or an ethyl group.
[0075] Examples of the compound represented by formula (I) include compounds represented by formula (Ia-1), formula (Ia-2), formula (Ib-1), formula (Ib-2), formula (Ic-1), and formula (Ic-2). n, R, and R in formula (Ia-1), formula (Ia-2), formula (Ib-1), formula (Ib-2), formula (Ic-1), and formula (Ic-2) are: 2 , L and m have the same meanings as above.
[0076]
[0077] In formula (Ia-1), formula (Ia-2), formula (Ib-1), formula (Ib-2), formula (Ic-1) and formula (Ic-2), at least one of the two Ls is preferably an alkanediyl group, and both are more preferably alkanediyl groups. In this case, the number of carbon atoms in the alkanediyl group is preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, and even more preferably 1 or 2.
[0078] In formula (Ia-1), formula (Ia-2), formula (Ib-1), formula (Ib-2), formula (Ic-1) and formula (Ic-2), two m's are each independently 0 or 1, preferably 0. More preferably, both m's are 0.
[0079] The two n are each independently any integer of 0 to 3, preferably any integer of 0 to 2, and more preferably 0 or 1. It is further preferred that both of the two n are 0.
[0080] In Formula (Ia-1), Formula (Ia-2), Formula (Ib-1), Formula (Ib-2), Formula (Ic-1) and Formula (Ic-2), two R 2 Each independently is preferably a hydrogen atom or a monovalent aliphatic chain hydrocarbon group, more preferably a hydrogen atom or a monovalent aliphatic chain hydrocarbon group having 1 to 6 carbon atoms, further preferably a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and particularly preferably a hydrogen atom, a methyl group or an ethyl group. 2 Preferably the same.
[0081] Specific examples of compound (I) are shown below, but the invention is not limited thereto.
[0082]
[0083]
[0084]
[0085]
[0086]
[0087]
[0088]
[0089]
[0090] From the viewpoint of synthesis, the molecular weight of compound (I) is preferably 2000 or less, more preferably 1000 or less, and further preferably 500 or less. From the viewpoint of volatility, the molecular weight is preferably 50 or more, more preferably 100 or more, and further preferably 150 or more.
[0091] <Method for producing compound>
[0092] Compound (I) can be produced by a method comprising the first step or the first and second steps shown below.
[0093] Step 1: a step of reacting a compound represented by formula (II) with a compound represented by formula (III) to obtain a compound represented by formula (I) wherein A is an O atom;
[0094] Step 2: A step of obtaining a compound represented by the formula (I) in which A is an S atom by reacting the compound represented by the formula (I) in which A is an O atom with a sulfiding agent.
[0095]
[0096] [In formula (II), n and R have the same meanings as above.
[0097] The two -SH groups in formula (II) are bonded to the 1-position and 6-position, 2-position and 6-position, or 2-position and 7-position of the naphthalene ring.]
[0098]
[0099] [In formula (III), R 2 , L and m have the same meanings as above, and X represents a leaving group.]
[0100] The reaction of the compound represented by formula (II) (hereinafter also referred to as "compound (II)") and the compound represented by formula (III) (hereinafter also referred to as "compound (III)") in the first step can be carried out in the presence of a base, for example. Two or more bases may be used in combination. Examples of the base include inorganic bases such as sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, sodium carbonate, potassium carbonate, lithium carbonate, cesium carbonate, sodium hydride, lithium aluminum hydride, sodium borohydride, sodium bicarbonate, potassium bicarbonate, lithium bicarbonate, and cesium bicarbonate; metal alkoxides such as sodium methoxide, potassium methoxide, lithium methoxide, sodium ethoxide, potassium ethoxide, sodium isopropoxide, potassium isopropoxide, sodium tert-butoxide, and potassium tert-butoxide; and organic bases such as ammonia, methylamine, dimethylamine, trimethylamine, triethylamine, diisopropylethylamine, triisopropylamine, DBU, DABCO, pyridine, 2,6-lutidine, 2,6-di-tert-butylpyridine, dimethylaminopyridine, triphenylphosphine, tetramethylammonium bromide, and tetramethylammonium chloride. The amount of the base used is, for example, 0.01 to 10 mol, preferably 0.5 to 5 mol, relative to 1 mol of compound (II).
[0101] In formula (III), as the leaving group represented by X, halogen atoms such as fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms can be cited; alkyl sulfonyl groups such as methylsulfonyl, ethylsulfonyl, propylsulfonyl, butylsulfonyl, trifluoromethylsulfonyl, perfluoroethylsulfonyl, perfluoropropylsulfonyl, and perfluorobutylsulfonyl; aryl sulfonyl groups such as phenylsulfonyl, p-toluenesulfonyl, p-fluorophenylsulfonyl, and pentafluorophenylsulfonyl. An example of compound (III) is an epihalohydrin compound (a compound in which X is a halogen atom, L is a methylene group, and m is 0). The amount of compound (III) used is, for example, 0.01 to 20 moles, preferably 0.5 to 15 moles, relative to 1 mole of compound (II). Two or more compounds (III) can also be used to implement the first step.
[0102] The reaction of compound (II) and compound (III) is preferably carried out in a solvent. As the solvent, in addition to water, organic solvents such as ketones, aromatic hydrocarbons, halogenated aromatic hydrocarbons, aliphatic hydrocarbons, halogenated aliphatic hydrocarbons, ethers, alcohols, glycol dimethyl ethers, esters, aliphatic nitriles, sulfoxides, and amides can also be mentioned. It is also possible to use two or more solvents in combination. As the organic solvent, specifically, the following solvents can be exemplified.
[0103] Ketones: acetone, methyl ethyl ketone, diethyl ketone, butyl methyl ketone, diisobutyl ketone, methyl isobutyl ketone, methyl isoamyl ketone, 2-heptanone, 2-octanone, cyclopentanone, cyclohexanone, etc.
[0104] Aromatic hydrocarbons: benzene, toluene, xylene, mesitylene, naphthalene, anisole, nitrobenzene, aniline, tetralin, durene, etc.
[0105] Halogenated aromatic hydrocarbons: chlorobenzene, dichlorobenzene, chloronaphthalene, etc.
[0106] Aliphatic hydrocarbons: pentane, hexane, heptane, etc.
[0107] Halogenated aliphatic hydrocarbons: dichloromethane, chloroform, 1,2-dichloroethane, tetrachloroethane, etc.
[0108] Ethers: diethyl ether, diisopropyl ether, methyl tert-butyl ether, cyclopentyl methyl ether, diphenyl ether, dimethoxyethane, dioxane, etc.
[0109] Alcohols: methanol, ethanol, propanol, isopropanol, butanol, tert-butanol, hexanol, cyclohexanol, ethylene glycol, propylene glycol, hexafluoroisopropanol, etc.
[0110] Glyme: diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, diethylene glycol butyl methyl ether, etc.
[0111] Esters: methyl acetate, ethyl acetate, propyl acetate, butyl acetate, etc.
[0112] Aliphatic nitriles: acetonitrile, etc.
[0113] Sulfoxides: dimethyl sulfoxide, sulfolane, etc.
[0114] Amides: N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, etc.
[0115] The reaction temperature of compound (II) and compound (III) is, for example, -80 to 200° C., preferably 0 to 150° C. The compound represented by formula (I) in which A is an O atom obtained by the reaction may be isolated or may be subjected to the second step without isolation.
[0116] The reaction carried out in the second step is a reaction in which the oxygen atom of the epoxy group or the oxetanyl group of the compound represented by the formula (I) in which A is an O atom is replaced with a sulfur atom using a vulcanizing agent, thereby forming a thiirane group (epithio group) or a thitanyl group. Examples of the vulcanizing agent include thiourea, methylthiourea, dimethylthiourea, trimethylthiourea, tetramethylthiourea, tetraethylthiourea, ethylenethiourea, sodium thiocyanate, potassium thiocyanate, and the like. The amount of the vulcanizing agent used is, for example, 0.01 to 20 mol, preferably 0.5 to 10 mol, relative to 1 mol of the compound represented by the formula (I) in which A is an O atom.
[0117] The reaction of the compound represented by formula (I) in which A is an O atom and the sulfiding agent is preferably carried out in a solvent. As the solvent, the organic solvents exemplified above can be used. Two or more organic solvents can also be used in combination. The temperature of the reaction of the compound represented by formula (I) in which A is an O atom and the sulfiding agent is, for example, -80 to 200°C, preferably 0 to 100°C.
[0118] In the second step, a polymerization inhibitor may be added to inhibit the polymerization of the generated compound represented by formula (I) in which A is a S atom. Examples of the polymerization inhibitor include acids and acid anhydrides. Specifically, the following substances may be used, and multiple substances may be used in combination:
[0119] Inorganic acidic compounds such as nitric acid, hydrochloric acid, perchloric acid, hypochlorous acid, chlorine dioxide, hydrofluoric acid, sulfuric acid, oleum, sulfonyl chloride, boric acid, arsenic acid, arsenous acid, pyroarsenic acid, phosphoric acid, phosphorous acid, hypophosphorous acid, phosphorus oxychloride, phosphorus oxybromide, phosphorus sulfide, phosphorus trichloride, phosphorus tribromide, phosphorus pentachloride, hydrocyanic acid, chromic acid, nitric anhydride, sulfuric anhydride, boron oxide, arsenic pentoxide, phosphorus pentoxide, chromic anhydride, silicon dioxide, aluminum oxide, aluminum chloride, zinc chloride, lithium hydrogen phosphate, sodium hydrogen phosphate, potassium hydrogen phosphate, cesium hydrogen phosphate, lithium dihydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, and cesium dihydrogen phosphate;
[0120] Organic carboxylic acids such as formic acid, acetic acid, peracetic acid, thioacetic acid, oxalic acid, tartaric acid, propionic acid, butyric acid, succinic acid, valeric acid, caproic acid, octanoic acid, cycloalkane acid, methyl mercaptopropionate, malonic acid, glutaric acid, adipic acid, cyclohexanecarboxylic acid, thiodipropionic acid, dithiodipropionic acid, maleic acid, benzoic acid, phenylacetic acid, o-toluic acid, m-toluic acid, p-toluic acid, salicylic acid, 2-methoxybenzoic acid, 3-methoxybenzoic acid, benzoylbenzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, benzilic acid, α-naphthoic acid, β-naphthoic acid, acetic anhydride, propionic anhydride, butyric anhydride, succinic anhydride, maleic anhydride, benzoic anhydride, phthalic anhydride, pyromellitic anhydride, trimellitic anhydride, and trifluoroacetic anhydride;
[0121] Phosphoric acids such as mono-, di- and tri-methyl phosphate, mono-, di- and tri-ethyl phosphate, mono-, di- and tri-isobutyl phosphate, mono-, di- and tri-butyl phosphate, mono-, di- and tri-lauryl phosphate, and phosphorous acids obtained by converting the phosphate moieties thereof into phosphites;
[0122] Organophosphorus compounds such as dialkyl dithiophosphoric acids represented by dimethyl dithiophosphoric acid;
[0123] Phenol, catechol, tert-butylcatechol, 2,6-di-tert-butylcresol, 2,6-di-tert-butylethylphenol, resorcinol, hydroquinone, phloroglucinol, pyrogallol, cresol, ethylphenol, butylphenol, nonylphenol, hydroxyphenylacetic acid, hydroxyphenylpropionic acid, hydroxyphenylacetamide, methyl hydroxyphenylacetate, ethyl hydroxyphenylacetate, hydroxyphenylethanol, hydroxyphenylethylamine, hydroxybenzaldehyde, phenylphenol, bisphenol-A, 2,2'-methylene-bis(4-methyl-6-tert-butylphenol), bisphenol-F, bisphenol-S, α-naphthol, β-naphthol, aminophenol, chlorophenol, 2,4,6-trichlorophenol and other phenols;
[0124] Sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, butanesulfonic acid, dodecanesulfonic acid, benzenesulfonic acid, o-toluenesulfonic acid, m-toluenesulfonic acid, p-toluenesulfonic acid, ethylbenzenesulfonic acid, butylbenzenesulfonic acid, dodecylbenzenesulfonic acid, p-phenolsulfonic acid, o-cresolsulfonic acid, m-aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, 4B acid, diaminostilbenesulfonic acid, biphenylsulfonic acid, α-naphthalenesulfonic acid, β-naphthalenesulfonic acid, perisulfonic acid, Laurentic acid, phenyl J acid, etc.
[0125] The amount of the polymerization inhibitor used is, for example, 0.0001 to 1.0 mol, preferably 0.01 to 0.2 mol, relative to 1 mol of the compound represented by the formula (I) in which A is an O atom. Preferred polymerization inhibitors include acetic acid, acetic anhydride, maleic acid, maleic anhydride, phosphoric acid, alkali metal hydrogen phosphate, and alkali metal dihydrogen phosphate.
[0126] In the second step, by washing the product solution after the reaction with an acidic aqueous solution, the stability over time of the compound represented by the formula (I) in which A is a S atom can be improved. As a specific example of the acid used in the acidic aqueous solution, the acid exemplified as a polymerization inhibitor in the above text can be cited. The acid can be used alone or in combination with two or more. The above-mentioned acidic aqueous solution usually exhibits an effect below pH 6, but the more effective range is below pH 3. Preferably, it is an aqueous solution of hydrochloric acid, sulfuric acid, phosphoric acid and / or maleic acid.
[0127] In addition, in the second step, in order to improve the stability of the compound represented by the formula (I) in which A is a S atom, a hydrogen sulfide adsorbent may be used. Examples of the hydrogen sulfide adsorbent include iron (III) hydroxide, zinc oxide, KNK-301 (zinc oxide adsorbent, manufactured by Kureha Oil & Fats Industries), NIONON 202A (iron oxide adsorbent, manufactured by Ibuki Masa Co., Ltd.), and LIMONIC (iron hydroxide adsorbent, manufactured by Japan LIMONIC). The hydrogen sulfide adsorbent may be added during the reaction in the second step, or may be used in the purification after the reaction.
[0128] <Composition>
[0129] The composition of the present invention (hereinafter, also referred to as "composition (I)") comprises compound (I), usually comprising compound (I) and other components other than compound (I). Composition (I) may comprise two or more compounds (I). For composition (I), in order to facilitate the curing of compound (I), curing may be performed by irradiation with active energy rays or heating. By curing composition (I), a molded article comprising a cured product of composition (I) can be formed. The molded article comprising the above-mentioned cured product is an article comprising the above-mentioned cured product, and refers to an article molded into a desired shape.
[0130] Since the composition (I) contains the compound (I), it can show a high refractive index and excellent curability. In addition, the composition (I) can show excellent heat resistance. In addition, the composition (I) can show excellent storage stability.
[0131] The content of compound (I) in composition (I) is preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 5% by mass or more, relative to the total amount of solid components of composition (I). It may be 100% by mass or less, preferably 99% by mass or less, more preferably 95% by mass or less, and may be 90% by mass or less or 80% by mass or less.
[0132] The total amount of the solid content of the composition (I) refers to the total amount of the components contained in the composition (I) except the solvent. The content of each component in the solid content of the composition can be measured by known analytical methods such as liquid chromatography or gas chromatography. The content of each component in the solid content of the composition (I) can also be calculated based on the formulation when the composition is prepared.
[0133] As the above-mentioned other components contained in the composition (I), for example, resins, curable compounds other than compound (I), polymerization initiators, solvents, polymerization inhibitors, other additives, etc. can be cited. As other additives, for example, inorganic particles, fillers, polymerization initiation aids, sensitizers, leveling agents, stabilizers, surfactants, antistatic agents, lubricants, antifouling agents, ultraviolet absorbers, antioxidants, dispersants, etc. can be cited. The composition (I) can include more than two of the above-mentioned other components. When the composition (I) includes additives, more than two additives can also be used in combination.
[0134] (1) Resin
[0135] The composition (I) may contain one or more resins. By making the composition (I) contain a resin, it is possible to impart developability to the cured product of the composition (I), or to adjust the mechanical properties and / or optical properties of the cured product and a molded product containing the same. As the resin, thermoplastic resins and curable resins may be mentioned. The curable resin may be a photocurable resin cured by irradiation with active energy rays, or a thermosetting resin cured by heat.
[0136] As thermoplastic resin, for example, olefin resins such as polyethylene resin, polypropylene resin, polycycloolefin resin, (meth) acrylic resins such as poly (meth) acrylic ester resin, polystyrene resin, styrene-acrylonitrile resin, acrylonitrile-butadiene-styrene resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyvinyl acetate resin, polyvinyl butyral resin, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol resin, polyethylene terephthalate resin, polybutylene terephthalate resin, polyester resins such as liquid crystal polyester resin, polyacetal resin, polyamide resin, polycarbonate resin, polyurethane resin, polyphenylene sulfide resin, etc. can be enumerated. One or more of these resins can also be made into polymer blends or polymer alloys for use.
[0137] As the curable resin, there can be mentioned a resin having a photopolymerizable group or a thermally polymerizable group, for example, (meth) acrylic resin, epoxy resin, melamine resin, unsaturated polyester resin, phenolic resin, urea resin, alkyd resin, polyimide resin, etc. In this specification, so-called (meth) acrylic acid refers to acrylic acid and / or methacrylic acid. The same is true for "(meth) acryloyl", "(meth) acrylate", etc.
[0138] As the resin, an alkali-soluble resin can be mentioned. By making the composition (I) contain an alkali-soluble resin, it is possible to impart developability to the cured product of the composition (I). The so-called alkali-soluble resin refers to a resin that is soluble in an alkaline aqueous solution. Specifically, for example, there is a resin having a carboxyl group and / or a phenolic hydroxyl group.
[0139] From the viewpoint of improving the developability and solvent resistance of the cured product of the composition (I), the acid value of the alkali-soluble resin is preferably 10 to 170 mgKOH / g, more preferably 20 to 150 mgKOH / g, and further preferably 30 to 140 mgKOH / g. The acid value is a value measured as the amount (mg) of potassium hydroxide required to neutralize 1 g of the alkali-soluble resin, and can be determined, for example, by titration using an aqueous potassium hydroxide solution.
[0140] In addition, as another example of the resin, there is a high refractive index resin. The high refractive index resin refers to a resin having a refractive index of 1.60 or more at a wavelength of 550 nm.
[0141] The weight average molecular weight (Mw) of the resin measured by gel permeation chromatography (GPC) in terms of standard polystyrene is, for example, 1000 to 9000, preferably 2000 to 8500, more preferably 3000 to 8500. In order to adjust the Mw of the resin to the above range, the reaction conditions such as the selection of the raw materials used, the charging method, the reaction temperature and time can be appropriately combined and adjusted.
[0142] When the composition (I) contains a resin, the content of the resin in the composition (I) is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, relative to the total amount of the solid content of the composition (I).
[0143] (2) Curable compounds other than compound (I)
[0144] The composition (I) may contain one or more curable compounds other than the compound (I). By making the composition (I) contain a curable compound other than the compound (I), the viscosity or curability of the composition (I) can be adjusted, or the mechanical properties and / or optical properties of the obtained cured product and the molded product containing the same can be adjusted.
[0145] Examples of curable compounds other than compound (I) include episulfide compounds other than compound (I), epoxy compounds other than compound (I), oxetane compounds, hydroxy compounds, vinyl ether compounds, allyl compounds, thiol compounds, polyphenol compounds, iso(thio)cyanate compounds, and (meth)acrylate compounds.
[0146] When the composition (I) contains a curable compound other than the compound (I), the content of the curable compound in the composition (I) is preferably 1% by mass or more, more preferably 2% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, relative to the total amount of the solid content of the composition (I).
[0147] (3) Polymerization initiator
[0148] The composition (I) may contain one or more polymerization initiators. As a polymerization initiator, there is no particular limitation as long as it can initiate the polymerization of compound (I), for example, free radical polymerization initiator, cationic polymerization initiator, anionic polymerization initiator, free radical and cationic polymerization initiator, etc. can be mentioned, which can be appropriately selected and used. Free radical polymerization initiator, cationic polymerization initiator, anionic polymerization initiator utilizes at least one of active energy ray irradiation and heat to generate free radicals, acids or bases, respectively, so that free radical polymerization, cationic polymerization or anionic polymerization of compound (I) can be carried out. It should be noted that compound (I) can also be polymerized and cured by utilizing at least one of active energy ray irradiation and heat in the absence of a polymerization initiator.
[0149] Examples of thermal radical polymerization initiators that initiate radical polymerization by heat include organic peroxides such as hydrogen peroxide and perbenzoic acid, and azo compounds such as azobisbutyronitrile. Examples of photoradical polymerization initiators that initiate radical polymerization by irradiation with active energy rays include oxime compounds, alkylphenone compounds, arylketone compounds, biimidazole compounds, triazine compounds, and acylphosphine compounds.
[0150] Cationic polymerization initiators are compounds that can release substances that initiate cationic polymerization by at least one of active energy ray irradiation and heat. Examples of cationic polymerization initiators include aromatic iodonium salts, aromatic sulfonium salts, aromatic ammonium salts, and cyclopentadienyl iron (II) complexes. Depending on the structure, they can initiate cationic polymerization by either or both of active energy ray irradiation and heat. Compounds that can release substances that initiate cationic polymerization by active energy ray irradiation are called photocationic polymerization initiators, and compounds that can release substances that initiate cationic polymerization by heat are called thermal cationic polymerization initiators.
[0151] Anionic polymerization initiators are compounds that can release substances that initiate anionic polymerization by irradiation with active energy rays and heat. As anionic polymerization initiators, ammonium salts, DBU (diazabicycloundecenium) salts, DBN (diazabicyclononenium) salts, biguanidium salts, aromatic phosphonium salts, aromatic dimethyl urea, aliphatic dimethyl urea, etc. can be cited. Depending on the difference in structure, they can initiate anionic polymerization by irradiation with active energy rays or heat or both. Compounds that can release substances that initiate anionic polymerization by irradiation with active energy rays are called photoanionic polymerization initiators, and compounds that can release substances that initiate anionic polymerization by heat are called thermal anionic polymerization initiators.
[0152] When the composition (I) contains a polymerization initiator, from the viewpoint of improving the heat resistance of the composition (I) and its cured product, the composition (I) preferably contains a thermal cationic polymerization initiator or a thermal anionic polymerization initiator, and more preferably contains a thermal anionic polymerization initiator.
[0153] When the composition (I) contains a polymerization initiator, the content of the polymerization initiator in the composition (I) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, from the viewpoint of improving curability and / or heat resistance, relative to 100 parts by mass of the total of compound (I) and other curable compounds, and is preferably 10% by mass or less, more preferably 8% by mass or less, from the viewpoint of improving the physical properties such as mechanical properties of the cured product.
[0154] (4) Solvent
[0155] Composition (I) may contain one or more solvents. As the solvent, in addition to the solvents described above, ether ester solvents such as methyl methoxyacetate, ethyl methoxyacetate, methyl 3-methoxypropionate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and ethylene glycol monomethyl ether acetate may be mentioned.
[0156] The solvent is preferably a solvent capable of dissolving or dispersing compound (I), and more preferably a solvent capable of dissolving or dispersing other components in addition to compound (I). As the solvent, for example, the organic solvents exemplified above can be used.
[0157] The content of the solvent in the composition (I) is the ratio of the total mass of all solvents contained in the composition (I) relative to the total amount of the composition (I). When the composition (I) contains a solvent, the content of the solvent in the composition (I) is preferably 60 parts by mass or more, more preferably 80 parts by mass or more, and preferably 1000 parts by mass or less, more preferably 500 parts by mass or less, relative to 100 parts by mass of the solid content of the composition (I). When the composition (I) contains a solvent, the solid content concentration of the composition (I) is preferably 5 to 60% by mass, more preferably 10 to 50% by mass.
[0158] (5) Polymerization inhibitor
[0159] The composition (I) may contain one or more polymerization inhibitors. As to whether or not to contain a polymerization inhibitor in the composition (I), when the composition (I) contains a polymerization initiator, it is preferably determined in consideration of the type of the polymerization initiator. The polymerization inhibitor is preferably a polymerization inhibitor that can be dissolved or dispersed in a solvent. The polymerization inhibitor contained in the composition (I) may be a polymerization inhibitor contained in the composition (I) together with the compound (I) when preparing the composition (I), or may be a polymerization inhibitor added in the second step when manufacturing the compound (I). By making the composition (I) contain a polymerization inhibitor, the undesired polymerization of the compound (I) can be suppressed, and therefore, the storage stability of the composition (I) can be improved.
[0160] When the composition (I) contains a polymerization inhibitor, the content of the polymerization inhibitor in the composition (I) is preferably from 0.0001 to 100 parts by mass, more preferably from 0.001 to 50 parts by mass, further preferably from 0.1 to 25 parts by mass, and even more preferably from 0.5 to 10 parts by mass, relative to 100 parts by mass of the compound (I), from the viewpoint of improving the storage stability of the composition (I).
[0161] Examples of the polymerization inhibitor contained in the composition (I) include the polymerization inhibitors exemplified above as the polymerization inhibitors that can be used in the second step when producing the compound (I), preferably carboxylic acids, more preferably formic acid and / or acetic acid.
[0162] <Solidified and molded products>
[0163] The present invention provides a solidified product of a compound (I) or a composition (I), and a molded product comprising the solidified product. The film-forming property and curability of the compound (I) and the composition (I) are excellent, and therefore, they are suitable as curable materials for making a solidified product or a molded product comprising the same. The solidified product can be obtained by curing the compound (I) or the composition (I) by utilizing at least any one of active energy ray irradiation and heat. The shape of the molded product comprising the solidified product is not particularly limited, and can be any shape corresponding to the use of the molded product, such as a film, a plate, a lens, a powder, a granular, a non-spherical particle, a broken particle, a porous shape, a block continuum, a fiber, a tubular, a hollow filament, etc.
[0164] The cured product of the composition (I) and the molded product containing the cured product can show a high refractive index because the composition (I) contains the compound (I). In addition, the cured product of the composition (I) and the molded product containing the cured product can show excellent heat resistance.
[0165] The method for obtaining a molded product from the composition (I) is not particularly limited, and examples thereof include a method of forming a film on a substrate and then molding by etching or the like, an injection molding method, and a cast polymerization molding method.
[0166] In the cast polymerization molding method, for example, the compound (I) or the composition (I) is injected into a molding die, degassing is performed as needed, and then the molded product is cured by heating in an oven, etc., and the molded product is taken out. The molded product taken out may be further irradiated with active energy rays for additional curing.
[0167] In the case of forming a film as a molded object on a substrate, compound (I) or composition (I) can be applied to a substrate, dried as needed to form a coating layer, and the coating layer is cured to obtain a molded object as a cured film. The molded object can also be a patterned cured film. Patterning can be performed by using methods such as photolithography, inkjet method, printing method, etc., to obtain a patterned cured film. The patterning method is preferably photolithography. Photolithography is the following method: compound (I) or composition (I) is applied to a substrate, dried as needed to form a coating layer, exposed to the coating layer across a photomask, and then developed.
[0168] As the substrate, quartz glass, borosilicate glass, aluminosilicate glass, soda lime glass with silica coated on the surface, resin plates such as polycarbonate, polymethyl methacrylate, polyethylene terephthalate, silicon, and substrates formed with thin films of aluminum, silver, silver / copper / palladium alloy, etc. on the above substrates can be used. Examples of the method for coating the compound (I) or the composition (I) on the substrate include spin coating, slit coating, slit and spin coating, etc.
[0169] As the light source used in the exposure, a light source that generates light with a wavelength of 250 nm or more and 450 nm or less is preferred. For example, a bandpass filter can be used to selectively extract light near 436 nm, near 408 nm, or near 365 nm from the light of the wavelength according to the absorption wavelength of the photopolymerization initiator. Specifically, mercury lamps, light emitting diodes, metal halide lamps, halogen lamps, etc. can be cited as the light source. Heating (pre-development baking) can also be performed after the pattern is exposed and before development.
[0170] As the developer used in the development, for example, aqueous solutions of alkaline compounds such as potassium hydroxide, sodium bicarbonate, sodium carbonate, and tetramethylammonium hydroxide, and organic solvents can be cited. As the organic solvent, organic solvents such as ketones, aromatic hydrocarbons, halogenated aromatic hydrocarbons, aliphatic hydrocarbons, halogenated aliphatic hydrocarbons, ethers, alcohols, glycol dimethyl ethers, esters, aliphatic nitriles, sulfoxides, and amides can be cited. It is also possible to use two or more solvents in combination. The developer may contain a surfactant. The development method may be any method such as a spin-on immersion method, an immersion method, and a spray method. The patterned film obtained by the development may also be further heated (post-baked).
[0171] The cured product or the molded product containing the cured product is formed by the compound (I) or the composition (I) containing the compound (I), and therefore, can show a high refractive index. In addition, their refractive index can be controlled to a desired refractive index by adjusting the composition of the composition (I), etc. The refractive index of the cured product or the molded product containing the same at a wavelength of 550nm can be 1.65 or more, 1.68 or more, 1.70 or more, 1.72 or more, and 1.75 or more. The refractive index at a wavelength of 550nm is, for example, 1.80 or less, or 1.78 or less.
[0172] [use]
[0173] According to the present invention, a cured product or a molded product having a high refractive index, or a cured product or a molded product having a desired refractive index can be obtained. Examples of uses of the cured or molded product include glass substitutes and surface coating materials thereof; coating materials for window glass, lighting glass, and light source protection glass of residences, facilities, transportation equipment, etc.; window films of residences, facilities, transportation equipment, etc.; interior and exterior decorative materials and interior and exterior decorative coatings of residences, facilities, transportation equipment, etc., and coating films formed using the coatings; alkyd resin spray paints and coating films formed using the coatings; acrylic spray paints and coating films formed using the coatings; components for light sources emitting ultraviolet light such as fluorescent lamps and mercury lamps; materials for blocking electromagnetic waves generated from precision machinery, components for electronic and electrical equipment, and various displays; containers or packaging materials for food, chemicals, and pharmaceuticals; sheets or films for bottles, boxes, blisters, cups, special packaging, laser disc coatings, and agricultural industry; anti-fading agents for printed materials, dyed materials, dyes, pigments, etc.; protective films for polymer supports (e.g., for plastic components such as machinery and automobile parts); printed material protective layers; inkjet media coatings; laminated matte materials; optical light sheets (optical light sheets); light film); safety glass / windshield interlayer; electrochromic / photochromic applications; overlaminate film; solar heat control film; cosmetics such as sunscreen, shampoo, hair dye (rinse), and hair treatment; fiber products and fibers for clothing such as sportswear, stockings, and hats; home interior decorations such as curtains, carpets, and wallpaper; medical devices such as plastic lenses, contact lenses, and artificial eyes; optical products such as optical filters, backlight display films, prisms, lenses (for example, eyeglass lenses, camera lenses, and microlenses and pickup lenses described below), mirrors, and photographic materials; stationery such as mold films, transfer stickers, anti-graffiti films, tapes, and inks; signboards, markers, etc. and their surface coating materials; substrates used in optical devices, etc.; optical waveguides; holograms; various sealing components such as LED sealing components and semiconductor sealing components; various insulating components; and the like.
[0174] The molded article can be suitably used as an optical product, i.e., a lens, used in an optical device. Examples of optical devices include solid-state imaging devices and display devices. In solid-state imaging devices, lenses are used to improve the efficiency of focusing light into each photoelectric conversion element. In addition, in display devices, lenses are used to improve the efficiency of extracting light from pixels. The lens may be a microlens. As a display device, it can be suitably used in a liquid crystal display device, an organic EL display device, and the like.
[0175] As high refractive index materials, inorganic compounds such as zirconium oxide and titanium oxide are known in the past. However, in the case of making a molded object containing a high refractive index material formed of an inorganic compound, it is sometimes difficult to perform etching and the molding is not easy. In addition, the high refractive index material sometimes scatters during molding and causes pollution problems. By using the high refractive index material of the present invention as an organic compound, the above problems can be solved.
[0176] The compound (I) and composition (I) of the present invention can be applied to sealing materials. The sealing material of the present invention contains compound (I) or composition (I). The pattern forming property of the sealing material of the present invention is excellent. The sealing material of the present invention can form a cured product or its molded product with a small linear thermal expansion coefficient (CTE). In addition, the sealing material of the present invention can form a cured product or its molded product with low water absorption and high flexibility. The cured product or the molded product can be used as various sealing components such as LED sealing material components and semiconductor sealing components. The sealing component can also be a sealing film.
[0177] The sealing material of the present invention may contain compound (I) or composition (I), and other components. Other components include inorganic fillers, etc. The content of the inorganic filler is, for example, 0.5 to 10,000 parts by mass relative to 100 parts by mass of compound (I) or composition (I).
[0178] The compound (I) and composition (I) of the present invention can be applied to insulating materials. The insulating material of the present invention contains the compound (I) or the composition (I). The pattern forming property of the insulating material of the present invention is excellent. The insulating material of the present invention can form a cured product or a molded product thereof having excellent dielectric constant and dielectric loss tangent. In addition, the insulating material of the present invention can form a cured product or a molded product thereof having a small linear thermal expansion coefficient (hereinafter also recorded as CTE). The cured product or the molded product can be used as various insulating components. The insulating component can also be an interlayer insulating film.
[0179] The insulating material of the present invention may contain the compound (I) or the composition (I) and other components. Examples of other components include plasticizers, antioxidants, heat stabilizers, antistatic agents, and the like.
[0180] Example
[0181] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In the Examples, % and parts indicating the content or the amount used are based on mass unless otherwise specified.
[0182] [Example 1: Synthesis of the compound represented by formula (Ia-11)]
[0183]
[0184] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, and 30 parts of the compound represented by formula (IIa-1) (1,6-naphthalenedithiol), 165 parts of acetone, 45 parts of pure water, and 139 parts of the compound represented by formula (III-1) (epichlorohydrin) were added to the above flask and stirred in an ice bath for 15 minutes. Next, 15 parts of sodium hydroxide, 66 parts of acetone, and 203 parts of pure water were added to another flask, and after completely dissolving them, they were added dropwise to the above four-necked flask over 1 hour. After the addition, the temperature was raised to 30°C and stirred at 30°C for 2 hours. The obtained mixture was purified to obtain 46 parts of the compound represented by formula (Ia-11).
[0185] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ia-11).
[0186] 1 H-NMR (deuterated chloroform) δ: 8.37-8.39 (1H), 7.85 (1H), 7.39-7.70 (4H), 3.08-3.29 (5H), 2.94-2.98 (1H), 2.57-2.81 (3H), 2.39-2.41 (1H)
[0187] LC-MS: [M+H] + =305.5
[0188] [Example 2: Synthesis of the compound represented by formula (Ia-21)]
[0189]
[0190] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, 3 parts of the compound represented by formula (Ia-11), 30 parts of methanol, 30 parts of toluene, 0.05 parts of acetic anhydride, and 3.8 parts of thiourea were added to the flask, and stirred at room temperature for 24 hours. The obtained mixture was purified to obtain 2.5 parts of the compound represented by formula (Ia-21).
[0191] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ia-21).
[0192] 1H-NMR (deuterated chloroform) δ: 8.39-8.43 (1H), 7.86 (1H), 7.40-7.74 (4H), 3.40-3.53 (2H), 3.04-3.18 (2H), 2.78-2.96 (2H), 2.47-2.49 (1H), 2.35-2.36 (1H), 2.14-2.16 (1H), 1.93-1.94 (1H)
[0193] LC-MS: [M+H] + =337.5
[0194] [Example 3: Synthesis of the compound represented by formula (Ib-11)]
[0195]
[0196] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, and 5 parts of the compound represented by formula (IIb-1) (2,6-naphthalenedithiol), 28 parts of acetone, 7.5 parts of pure water, and 23 parts of the compound represented by formula (III-1) (epichlorohydrin) were added to the above flask and stirred in an ice bath for 15 minutes. Next, 2.5 parts of sodium hydroxide, 11 parts of acetone, and 34 parts of pure water were added to another flask, and after being completely dissolved, they were added dropwise to the above four-necked flask over 1 hour. After the addition, the temperature was raised to 65°C in an oil bath and stirred at 65°C for 1 hour. The obtained mixture was purified to obtain 7.5 parts of the compound represented by formula (Ib-11).
[0197] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ib-11).
[0198] 1 H-NMR (deuterated chloroform) δ: 7.81 (2H), 7.67-7.69 (2H), 7.47-7.50 (2H), 3.20-3.27 (4H), 3.02-3.09 (2H), 2.77-2.80 (2H), 2.55-2.57 (2H)
[0199] LC-MS: [M+H] + =305.5
[0200] [Example 4: Synthesis of the compound represented by formula (Ib-21)]
[0201]
[0202] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, and 5 parts of the compound represented by formula (Ib-11), 80 parts of methanol, 20 parts of dichloromethane, and 6.3 parts of thiourea were added to the flask and stirred at room temperature for 24 hours. The resulting mixture was purified to obtain 3.4 parts of the compound represented by formula (Ib-21).
[0203] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ib-21).
[0204] 1 H-NMR (deuterated chloroform) δ: 7.84-7.85 (2H), 7.68-7.71 (2H), 7.49-7.52 (2H), 3.51-3.56 (2H), 3.13-3.17 (2H), 2.89-2.95 (2H), 2.48-2.50 (2H), 2.13-2.15 (2H)
[0205] LC-MS: [M+H] + =337.5
[0206] [Example 5: Synthesis of the compound represented by formula (Ic-11)]
[0207]
[0208] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, and 15 parts of the compound represented by formula (IIc-1) (2,7-naphthalenedithiol), 83 parts of acetone, 23 parts of pure water, and 69 parts of the compound represented by formula (III-1) (epichlorohydrin) were added to the flask and stirred in an ice bath for 15 minutes. Next, 7.5 parts of sodium hydroxide, 33 parts of acetone, and 101 parts of pure water were added to another flask, and after being completely dissolved, they were added dropwise to the four-necked flask over 1 hour. After the addition, the temperature was raised to 65°C in an oil bath and stirred at 65°C for 1 hour. The resulting mixture was purified to obtain 24 parts of the compound represented by formula (Ic-11).
[0209] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ic-11).
[0210] 1 H-NMR (deuterated chloroform) δ: 7.70-7.76 (4H), 7.43-7.45 (2H), 3.21-3.27 (4H), 3.05-3.11 (2H), 2.78-2.80 (2H), 2.57-2.58 (2H)
[0211] LC-MS: [M+H] + =305.5
[0212] [Example 6: Synthesis of the compound represented by formula (Ic-21)]
[0213]
[0214] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, 20 parts of the compound represented by formula (Ic-11), 320 parts of methanol, 80 parts of dichloromethane, and 25 parts of thiourea were added to the flask, and stirred at room temperature for 24 hours. The resulting mixture was purified to obtain 18.1 parts of the compound represented by formula (Ic-21).
[0215] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ic-21).
[0216] 1 H-NMR (deuterated chloroform) δ: 7.73-7.79 (4H), 7.46-7.48 (2H), 3.52-3.57 (2H), 3.14-3.18 (2H), 2.90-2.96 (2H), 2.49-2.51 (2H), 2.15-2.17 (2H)
[0217] LC-MS: [M+H] + =337.5
[0218] [Example 7: Synthesis of the compound represented by formula (Ic-12)]
[0219]
[0220] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, and 5 parts of the compound represented by formula (IIc-1) (2,7-naphthalenedithiol), 28 parts of acetone, 7.5 parts of pure water, and 27 parts of the compound represented by formula (III-2) (2-(chloromethyl)-1,2-epoxypropane) were added to the flask, and stirred in an ice bath for 15 minutes. Next, 2.5 parts of sodium hydroxide, 11 parts of acetone, and 34 parts of pure water were added to another flask, and after they were completely dissolved, they were added dropwise to the four-necked flask over 1 hour. After the addition, the temperature was raised to 65°C in an oil bath, and stirred at 65°C for 1 hour. The resulting mixture was purified to obtain 8.3 parts of the compound represented by formula (Ic-12).
[0221] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ic-12).
[0222] 1 H-NMR (deuterated chloroform) δ: 7.68-7.71 (4H), 7.40-7.43 (2H), 3.11-3.26 (4H), 2.61-2.75 (4H), 1.47-1.49 (6H)
[0223] LC-MS: [M+H] + =333.5
[0224] [Example 8: Synthesis of the compound represented by formula (Ic-22)]
[0225]
[0226] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, 8 parts of the compound represented by formula (Ic-12), 128 parts of methanol, 32 parts of dichloromethane, and 9.2 parts of thiourea were added to the flask, and stirred at room temperature for 24 hours. The resulting mixture was purified to obtain 8.1 parts of the compound represented by formula (Ic-22).
[0227] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ic-22).
[0228] 1 H-NMR (deuterated chloroform) δ: 7.69-7.74 (4H), 7.41-7.44 (2H), 3.49-3.53 (2H), 3.24-3.27 (2H), 2.32-2.34 (4H), 1.75 (6H)
[0229] LC-MS: [M+H] + =365.5
[0230] [Example 9: Synthesis of the compound represented by formula (Ic-13)]
[0231]
[0232] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, and 1.5 parts of the compound represented by formula (IIc-1) (2,7-naphthalenedithiol), 8.3 parts of acetone, 2.3 parts of pure water, and 4.5 parts of the compound represented by formula (III-3) (2-(chloromethyl)-1,2-butylene oxide) were added to the above flask, and stirred in an ice bath for 15 minutes. Next, 0.75 parts of sodium hydroxide, 3.3 parts of acetone, and 10.1 parts of pure water were added to another flask, and after they were completely dissolved, they were added dropwise to the above four-necked flask over 1 hour. After the addition, the temperature was raised to 65°C using an oil bath, and stirred at 65°C for 1 hour. The resulting mixture was purified to obtain 2.5 parts of the compound represented by formula (Ic-13).
[0233] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ic-13).
[0234] 1 H-NMR (deuterated chloroform) δ: 7.66-7.69 (4H), 7.39-7.41 (2H), 3.27-3.36 (2H), 3.13-3.16 (2H), 2.63-2.69 (4H), 1.76-1.84 (4H), 0.93-0.98 (6H)
[0235] LC-MS: [M+H] + =361.5
[0236] [Example 10: Synthesis of the compound represented by formula (Ic-23)]
[0237]
[0238] A four-necked flask equipped with a Dimroth condenser and a thermometer was placed in a nitrogen atmosphere, 2.5 parts of the compound represented by formula (Ic-13), 39 parts of methanol, 10 parts of dichloromethane, and 2.6 parts of thiourea were added to the flask, and stirred at room temperature for 24 hours. The resulting mixture was purified to obtain 2.1 parts of the compound represented by formula (Ic-23).
[0239] LC-MS determination and 1 H-NMR analysis confirmed the formation of the compound represented by formula (Ic-13).
[0240] 1H-NMR (deuterated chloroform) δ: 7.67-7.73 (4H), 7.41-7.44 (2H), 3.60-3.64 (2H), 3.11-3.17 (2H), 2.41-2.43 (2H), 2.31-2.32 (4H), 1.48-1.57 (2H), 1.03-1.06 (6H)
[0241] LC-MS: [M+H] + =393.8
[0242] [Example 11: Preparation of composition]
[0243] 100 parts by mass of the compound represented by formula (Ia-11) obtained in Example 1, 5 parts by mass of polymerization initiator A, and 310 parts by mass of cyclopentanone as a solvent were placed in a flask and stirred to obtain a liquid composition. The composition was transparent when visually observed, and it was confirmed that the ingredients were uniformly dissolved.
[0244] [Examples 12 to 17, Examples 20 to 40, Comparative Examples 1 to 5]
[0245] The liquid composition was obtained in the same manner as in Example 11 except that the types of ingredients and their addition amounts in the composition were as shown in Table 1. The compositions of Examples 12 to 17, Examples 20 to 40, and Comparative Examples 1 and 3 were transparent when visually observed, and it was confirmed that the ingredients were uniformly dissolved. The compositions of Comparative Examples 2, 4, and 5 were turbid when visually observed, and it was confirmed that the ingredients were not uniformly dissolved.
[0246] [Example 18]
[0247] In this example, a liquid composition (containing only the compound represented by formula (Ia-21)) was obtained in the same manner as in Example 14 except that no polymerization initiator was used. The composition was transparent when visually observed, and it was confirmed that the ingredients were uniformly dissolved.
[0248] [Example 19]
[0249] In this example, a liquid composition was obtained in the same manner as in Example 14 except that 0.5 parts by mass of a sensitizer ("ANTHRACURE UVS-1331" manufactured by AirWater Performance Chemicals, Inc.) was added in addition to the polymerization initiators shown in Table 1. The composition was transparent when visually observed, and it was confirmed that the ingredients were uniformly dissolved.
[0250] The details of the abbreviations of the blending components shown in Table 1 are as follows.
[0251] [1] (Ia-11): A compound represented by formula (Ia-11)
[0252] [2] (Ia-21): A compound represented by formula (Ia-21)
[0253] [3] (Ib-11): A compound represented by formula (Ib-11)
[0254] [4] (Ib-21): A compound represented by formula (Ib-21)
[0255] [5] (Ic-11): A compound represented by formula (Ic-11)
[0256] [6] (Ic-21): A compound represented by formula (Ic-21)
[0257] [7] (Y1): A compound represented by the formula (Y1) (1,6-bis(glycidyloxy)naphthalene, "EPICLON HP-4032D" manufactured by DIC Corporation)
[0258]
[0259] [8] (Y2): A compound represented by the formula (Y2) (poly(1-vinylnaphthalene), manufactured by Sigma-Aldrich Co.)
[0260]
[0261] [9] (Y3): A compound represented by the formula (Y3) (bisphenol A diglycidyl ether, "EPICLON EXA-850CRP" manufactured by DIC Corporation)
[0262]
[0263]
[10] (Y4): A compound represented by the formula (Y4) (2,2'-diglycidyloxy-1,1'-binaphthyl, "DGOBINL" manufactured by SUGAI CHEMICAL INDUSTRY CO., LTD.)
[0264]
[0265]
[11] (Y5): A compound represented by the formula (Y5) (9-vinylcarbazole, manufactured by TCI Corporation)
[0266]
[0267]
[12] Polymerization initiator A: Sulfonium salt type photocationic polymerization initiator ("VC-1S" manufactured by San-Apro Co., Ltd.)
[0268]
[13] Polymerization initiator B: Sulfonium salt type photocationic polymerization initiator ("VC-1FG" manufactured by San-Apro Co., Ltd.)
[0269]
[14] Polymerization initiator C: Biguanidine salt type photoanionic polymerization initiator ("WPBG-300" manufactured by FUJIFILM Wako Pure Chemical Corporation)
[0270]
[15] Polymerization initiator D: Sulfonium salt type thermal cationic polymerization initiator ("SI-110" manufactured by Sanshin Chemical Industry Co., Ltd.)
[0271]
[16] Polymerization initiator E: Sulfonium salt type thermal cationic polymerization initiator ("SI-360" manufactured by Sanshin Chemical Industry Co., Ltd.)
[0272]
[17] Polymerization initiator F: Sulfonium salt type thermal cationic polymerization initiator ("SI-300" manufactured by Sanshin Chemical Industry Co., Ltd.)
[0273]
[18] Polymerization initiator G: Sulfonium salt type thermal cationic polymerization initiator ("TA-100" manufactured by San-Apro Co., Ltd.)
[0274]
[19] Polymerization initiator H: Sulfonium salt type thermal cationic polymerization initiator ("TA-100FG" manufactured by San-Apro Co., Ltd.)
[0275]
[20] Polymerization initiator I: ammonium salt type thermal cationic polymerization initiator (manufactured by KING INDUSTRIES INC., "CXC-1821")
[0276]
[21] Polymerization initiator J: ammonium salt type thermal cationic polymerization initiator ("CXC-1614" manufactured by KING INDUSTRIES INC.)
[0277]
[22] Polymerization initiator K: ammonium salt type thermal cationic polymerization initiator ("CXC-2689" manufactured by KING INDUSTRIES INC.)
[0278]
[23] Polymerization initiator L: DBU salt type thermal anionic polymerization initiator ("U-CATSA603" manufactured by San-Apro Co., Ltd.)
[0279]
[24] Polymerization initiator M: DBU salt type thermal anionic polymerization initiator ("U-CATSA102" manufactured by San-Apro Co., Ltd.)
[0280]
[25] Polymerization initiator N: DBU salt type thermal anionic polymerization initiator ("U-CAT5002" manufactured by San-Apro Co., Ltd.)
[0281]
[26] Polymerization initiator O: DBN salt type thermal anionic polymerization initiator ("U-CAT1102" manufactured by San-Apro Co., Ltd.)
[0282]
[27] Polymerization initiator P: ammonium salt type thermal anionic polymerization initiator ("U-CAT18X" manufactured by San-Apro Co., Ltd.)
[0283] [Evaluation test]
[0284] (1) Refractive index of cured product
[0285] (1-1) Formation of Cured Film 1 (Formation of Cured Film Using Compositions of Examples 11 to 17, Example 19, Comparative Example 1, and Comparative Examples 3 to 5)
[0286] About 3 cc of the composition prepared above was dropped onto an alkali-free glass (Eagle XG thickness 0.7 mm, manufactured by Corning) and spin-coated at 1000 rpm for 20 seconds using a spin coater (MS-B100, manufactured by MIKASA) to form a coating layer. The alkali-free glass plate with the coating layer was pre-baked at 60°C for 2 minutes. Next, a high-pressure mercury lamp proximity UV exposure device (UV-3300SC, manufactured by USHIO) was used to expose the glass in an atmospheric atmosphere at 1000 mJ / cm 2 The alkali-free glass plate with the coating layer formed thereon was exposed to an irradiation energy of . Next, the alkali-free glass plate with the coating layer formed thereon after exposure was heated at 120°C for 5 minutes as a post-bake to obtain an alkali-free glass with a cured film formed thereon. The film thickness of the cured film on the alkali-free glass was measured using a stylus film thickness meter (DekTak XT, manufactured by Bruker), and the result was 1.5 μm. The curing conditions of the coating layer are summarized in Table 1.
[0287] (1-2) Formation of Cured Film 2 (Formation of Cured Film Using Compositions of Example 18, Examples 20 to 40, and Comparative Example 2)
[0288] About 3cc of the composition prepared above was dropped onto an alkali-free glass (Eagle XG thickness 0.7mm, manufactured by Corning), and spin-coated using a spin coater (MS-B100, manufactured by MIKASA) at 1000rpm for 20 seconds to form a coating layer. The alkali-free glass plate having a coating layer formed thereon was heated at 60°C for 2 minutes as a pre-bake. Next, the alkali-free glass plate having a coating layer formed thereon was heated under the curing conditions described in Table 1 as a post-bake to obtain an alkali-free glass having a cured film formed thereon. The film thickness of the cured film on the alkali-free glass was measured using a stylus film thickness meter (DekTak XT, manufactured by Bruker), and the result was 1.5μm.
[0289] (1-3) Formation of Cured Film 3 (Formation of Cured Film Using Composition Containing Compound Synthesized in Example 8)
[0290] The compound 100 parts by mass, polymerization initiator A 5 parts by mass, and 310 parts by mass of cyclopentanone as solvent obtained in Example 8 are loaded into a flask and stirred to obtain a liquid composition. The composition is transparent when viewed visually, and it is confirmed that the ingredients are uniformly dissolved. About 3cc of the composition is added dropwise to alkali-free glass (EagleXG thickness 0.7mm, Corning company system), and spin-coated using a spin coater (MS-B100, MIKASA system) under the conditions of 1000rpm and 20 seconds to form a coating layer. For the alkali-free glass plate formed with a coating layer, it is heated at 60°C for 2 minutes as pre-baking. Next, for the alkali-free glass plate formed with a coating layer, it is heated at 120°C, 5 minutes of curing conditions as post-baking to obtain an alkali-free glass formed with a cured film. The film thickness of the cured film on the alkali-free glass was measured with a stylus film thickness meter (DekTak XT, manufactured by Bruker) and found to be 1.5 μm.
[0291] (1-4) Formation of Cured Film 4 (Formation of Cured Film Using Composition Containing Compound Synthesized in Example 10)
[0292] The compound represented by the formula (Ic-23) obtained in Example 10, 100 parts by mass, 5 parts by mass of polymerization initiator A, and 310 parts by mass of cyclopentanone as a solvent are loaded into a flask, stirred to obtain a liquid composition. The composition is transparent when viewed visually, and it is confirmed that the matching components have been uniformly dissolved. About 3cc of the composition is added dropwise to alkali-free glass (EagleXG thickness 0.7mm, Corning company system), and spin-coated using a spin coater (MS-B100, MIKASA system) under the conditions of 1000rpm and 20 seconds to form a coating layer. For the alkali-free glass plate formed with a coating layer, it is heated at 60°C for 2 minutes as a pre-bake. Next, for the alkali-free glass plate formed with a coating layer, it is heated at 120°C and 5 minutes under the curing conditions as a post-bake to obtain an alkali-free glass formed with a cured film. The film thickness of the cured film on the alkali-free glass was measured with a stylus film thickness meter (DekTak XT, manufactured by Bruker) and found to be 1.5 μm.
[0293] (1-5) Determination of refractive index
[0294] For the alkali-free glass formed with a cured film prepared in (1-1) and (1-2), a visible ultraviolet spectrophotometer (V-650, JASCO Corporation) with an integrating sphere unit (ISV-922, JASCO Corporation) was used to measure the transmission spectrum and reflection spectrum at wavelengths of 300 nm to 800 nm. The refractive index of the cured film at a wavelength of 550 nm was calculated based on the Fresnel formula (Hecht Optics I Original 5th Edition, Maruzen Publishing, 2018, p.209-p.226) according to the value of the wavelength 550 nm in the true reflection spectrum obtained by subtracting the increase and decrease caused by the interference of the reflection spectrum from the transmission spectrum and smoothing the increase and decrease caused by the interference of the reflection spectrum from the reflection spectrum. The results of Examples 11 to 40 and Comparative Examples 1 to 3 are shown in Table 1.
[0295] The refractive index of the alkali-free glass on which the cured film was formed, prepared in the above (1-3), was measured by the same method and found to be 1.70.
[0296] The refractive index of the alkali-free glass on which the cured film was formed, prepared in the above (1-4), was measured by the same method and found to be 1.68.
[0297] (2) Film-forming properties
[0298] (2-1) Compositions prepared in Examples 11 to 40 and Comparative Examples 1 to 5
[0299] For the compositions prepared in Examples 11 to 40 and Comparative Examples 1 to 5, a coating layer was formed by the following method, and the film-forming property was evaluated. About 3 cc of the composition was dropped onto an alkali-free glass (Eagle XG thickness 0.7 mm, manufactured by Corning), and spin-coated at 1000 rpm for 20 seconds using a spin coater (MS-B100, manufactured by MIKASA) to form a coating layer. Next, the alkali-free glass plate with the coating layer formed thereon was heated at 60°C for 2 minutes.
[0300] The obtained coating layer was observed, and the film-forming property of the composition was evaluated according to the following evaluation criteria. The results are shown in Table 1. The so-called open hole defect refers to the state where a hole-shaped alkali-free glass plate exposed portion with a diameter of 1 mm or more is generated on the coating layer. If the result is A, the film-forming property is good.
[0301] A: Colorless and transparent, without any hole defects or white turbidity
[0302] D1: There is an opening defect
[0303] D2: White turbidity
[0304] (2-2) Composition containing the compound synthesized in Example 8
[0305] 100 parts by mass of the compound represented by the formula (Ic-22) obtained in Example 8, 5 parts by mass of polymerization initiator A, and 310 parts by mass of cyclopentanone as a solvent are loaded into a flask and stirred to obtain a liquid composition. The composition is transparent when viewed visually, confirming that the matching components have been uniformly dissolved. About 3cc of the composition is added dropwise to an alkali-free glass (EagleXG thickness 0.7mm, Corning company system), and a spin coater (MS-B100, MIKASA system) is used to spin-coat at 1000rpm and 20 seconds to form a coating layer. The alkali-free glass plate formed with a coating layer is heated under the conditions of 60 ° C and 2 minutes.
[0306] The obtained coating layer was observed and confirmed to be colorless and transparent with no open hole defects or white turbidity.
[0307] (2-3) Composition containing the compound synthesized in Example 10
[0308] 100 parts by mass of the compound represented by the formula (Ic-23) obtained in Example 10, 5 parts by mass of polymerization initiator A, and 310 parts by mass of cyclopentanone as a solvent are loaded into a flask and stirred to obtain a liquid composition. The composition is transparent when viewed visually, confirming that the matching components have been uniformly dissolved. About 3cc of the composition is added dropwise to an alkali-free glass (EagleXG thickness 0.7mm, Corning company system), and a spin coater (MS-B100, MIKASA system) is used to spin-coat at 1000rpm and 20 seconds to form a coating layer. The alkali-free glass plate formed with a coating layer is heated at 60°C and 2 minutes.
[0309] The obtained coating layer was observed and confirmed to be colorless and transparent with no open hole defects or white turbidity.
[0310] (3) Curing
[0311] By the same method as in the above (1-1) and (1-2), alkali-free glass having a cured film formed thereon was obtained using the compositions of Examples 11 to 40 and Comparative Examples 1 to 3.
[0312] The obtained cured film was used to evaluate the curability of the composition according to the following evaluation criteria. The results are shown in Table 1. For curability, the alkali-free glass formed with the cured film was immersed in acetone at 23°C for 10 minutes, and the evaluation was performed based on the change in the appearance of the cured film before and after the immersion and the film thickness retention rate before and after the immersion (film thickness retention rate = film thickness after immersion ÷ film thickness before immersion). If the result is A or B, the curability is good.
[0313] A: No appearance change, film thickness retention rate is above 90% and below 100%
[0314] B: No appearance change, film thickness retention rate is 80% or more and less than 90%
[0315] C: No appearance change, film thickness retention rate is less than 80%
[0316] D: Regardless of the film thickness retention rate, the cured film is turbid after immersion
[0317] (4) Heat resistance
[0318] By the same method as in the above (1-1) and (1-2), alkali-free glass having a cured film formed thereon was obtained using the compositions of Examples 11 to 40 and Comparative Examples 1 to 3.
[0319] The obtained cured film was used to evaluate the heat resistance of the composition according to the following evaluation criteria. The results are shown in Table 1. For heat resistance, the alkali-free glass formed with the cured film was left to stand on a heating plate heated to 260°C for 5 minutes, and the transmittance change at a wavelength of 450nm of the cured film before and after heating (transmittance change = transmittance before heating - transmittance after heating) was evaluated. If the result is A or B, the heat resistance is good.
[0320] A: Transmittance change is less than 0% and less than 2%
[0321] B: Transmittance change is 2% or more and less than 5%
[0322] C: Transmittance change is less than 5% and less than 10%
[0323] [Table 1]
[0324]
[0325] (5) Storage stability
[0326] The compositions of Examples 11 to 32 and 40 prepared above were stored in brown bottles, and the storage stability of the compositions at room temperature (23° C.) was evaluated according to the following evaluation criteria. The results are shown in Table 2. If the result is A or B, the storage stability is good.
[0327] A: No turbidity was observed in the composition after 120 days.
[0328] B: After 90 days, the composition did not become cloudy, but after 120 days, the composition became cloudy.
[0329] C: No turbidity was observed in the composition after 60 days, but turbidity was observed in the composition after 90 days.
[0330] D: After 60 days, the composition becomes cloudy.
[0331] [Table 2]
[0332]
[0333] [Synthesis Example 1: Synthesis of the compound represented by formula (X-1)]
[0334]
[0335] [In the formula, A' represents an oxygen atom or a sulfur atom. n' is an average value and represents a number greater than 1.]
[0336] A four-necked flask equipped with a Dimroth condenser and a thermometer was set to a nitrogen atmosphere, and 20 parts of the compound represented by formula (X1-1) (naphthol-cresol Novolac type epoxy resin "NC-7000L" manufactured by Nippon Kayaku Co., Ltd.), 320 parts of dichloromethane, 80 parts of methanol, and 33 parts of thiourea were added to the flask and stirred at room temperature for 72 hours. The obtained mixture was purified to obtain 14 parts of the compound represented by formula (X-1).
[0337] conduct 1 H-NMR analysis (deuterated chloroform) confirmed the formation of the compound represented by formula (X-1). The peak at 2.56 to 2.96 ppm derived from the epoxy group completely disappeared, and the peak derived from thiirane was re-confirmed at 2.40 to 2.65 ppm.
[0338] According to the above 1 H-NMR analysis was performed to determine the ratio of the number of A' as sulfur atoms to the total number of A' (sulfur atom content ratio), and the average value was 1.0. In addition, the weight average molecular weight Mw of the compound represented by formula (X-1) obtained by GPC measurement was 1500, and the number average molecular weight was 600. The GPC measurement was performed under the following conditions.
[0339] Device: K2479 (manufactured by Shimadzu Corporation)
[0340] Column: SHIMADZU Shim-pack GPC-80M
[0341] Column temperature: 40°C
[0342] Solvent: Tetrahydrofuran
[0343] Flow rate: 1.0mL / min
[0344] Detector: RI
[0345] Calibration standard substances: TSK STANDARD POLYSTYRENE F-40, F-4, F-288, A-2500, A-500 (manufactured by TOSOH Corporation)
[0346] (7) Preparation of Film for Physical Property Measurement (Solidified Material for Physical Property Measurement)
[0347] A film (cured product) for measuring physical properties was produced as follows.
[0348] (7-1) Membrane for physical property measurement-1
[0349] 100 parts by mass of the compound represented by formula (Ia-21), 5 parts by mass of the compound represented by formula (X-1), 1 part by mass of a polymerization initiator (ammonium salt-type thermal cationic polymerization initiator ("CXC-1821" manufactured by KING INDUSTRIES INC.), and 50 parts by mass of propylene glycol monomethyl ether acetate as a solvent were placed in a flask and stirred to obtain a liquid composition. The composition was transparent when visually observed, confirming that the ingredients were uniformly dissolved.
[0350] The composition was dropped onto a polyimide film and coated with an applicator to form a coating layer. The film with the coating layer was heated at 120° C. for 30 minutes. After heating, the obtained film (film for physical property measurement-1) had a thickness of 260 μm.
[0351] (7-2) Composition for Physical Property Measurement-2
[0352] 50 parts by mass of the compound represented by formula (Ia-21), 50 parts by mass of the compound represented by formula (X-1), 1 part by mass of a polymerization initiator (ammonium salt-type thermal cationic polymerization initiator (“CXC-1821” manufactured by KING INDUSTRIES INC.), and 50 parts by mass of propylene glycol monomethyl ether acetate as a solvent were placed in a flask and stirred to obtain a liquid composition. The composition was transparent when visually observed, confirming that the ingredients were uniformly dissolved.
[0353] The composition was dropped onto a polyimide film and coated with an applicator to form a coating layer. The film with the coating layer was heated at 120° C. for 30 minutes. After heating, the obtained film (film for physical property measurement-2) had a thickness of 150 μm.
[0354] (8) Coefficient of thermal expansion (CTE)
[0355] The CTE of the film-1 or film-2 obtained above was measured using a thermomechanical analyzer (TMA) under the following conditions, and the CTE from 25°C to Tg (referred to as CTE1) and the CTE from Tg to 170°C (referred to as CTE2) were calculated. In addition, the glass transition temperature (Tg) was measured. The results are shown in Table 3.
[0356] Equipment: TMA / SS7100 manufactured by Hitachi High-Tech Science Corporation
[0357] Load: 50.0mN
[0358] Temperature program: from 20°C to 200°C at a rate of 5°C / min
[0359] Test piece: rectangular parallelepiped. Length 40 mm. Width 5 mm. Thickness: 260 μm for Physical Property Measurement Film-1 and 150 μm for Physical Property Measurement Film-2
[0360] (9) Dielectric loss tangent (Df) and relative dielectric constant (Dk)
[0361] A 50 mm x 50 mm sample was cut out from the above-obtained film-1 or film-2 for measuring physical properties, and Df and Dk were measured under the following conditions. The sample was humidity-adjusted for 24 hours under the conditions of 25°C / 55%RH, and then measured. The results are shown in Table 3.
[0362] Device: Compact USB vector network analyzer manufactured by Anritsu Corporation (product name: MS46122B)
[0363] Cavity resonator manufactured by AET Inc. (TE mode 10 GHz type)
[0364] Measurement frequency: 10 GHz
[0365] Measurement atmosphere: 23℃ / 50%RH
[0366] (10) Tensile elastic modulus
[0367] The above-obtained film-1 or film-2 for measuring physical properties was subjected to a tensile test under the conditions of a chuck distance of 22 mm and a speed of 10 mm / min, and the SS curve was measured, and the tensile modulus (GPa) at 25°C and 55% RH was calculated from the slope. The results are shown in Table 3.
[0368] Test piece: dumbbell test piece width 4mm, length 50mm
[0369] Device: "AUTOGRAPH AG-IS" manufactured by Shimadzu Corporation
[0370] (11) Flexural modulus
[0371] The above-obtained film-1 for measuring physical properties or film-2 for measuring physical properties was subjected to a three-point bending test under the conditions of a distance between lower supporting points of 20 mm and a speed of 1 mm / min, and the SS curve was measured, and the bending modulus (GPa) at 25°C and 55% RH was calculated from the slope thereof. The results are shown in Table 3.
[0372] Test piece: width 10mm, length 80mm
[0373] Device: "AUTOGRAPH AG-IS" manufactured by Shimadzu Corporation
[0374] [Table 3]
[0375] Membrane for physical property measurement-1 Membrane for physical property measurement-2 Tg(℃) 110 130 CTE1(ppm / K) 73.2 79 CTE2(ppm / K) 144 149 Df 0.00592 0.144 Dk 3.21 3.06 Tensile elastic modulus (GPa) 1.5 1.42 Flexural modulus (GPa) 2.48 4.10
Claims
1. A compound represented by formula (I), In formula (I), L represents a divalent group, and a plurality of Ls may be the same or different. m represents 0 or 1. There are multiple m's which can be the same or different. A represents an O atom or a S atom. Multiple A's may be the same or different. n represents any integer from 0 to 3, and multiple n's may be the same or different. R represents a monovalent substituent. When there are multiple Rs, the multiple Rs may be the same or different. R 2 represents a hydrogen atom or a monovalent substituent, and there are multiple R 2 Can be the same or different, In formula (I), two groups represented by the following formula are bonded to the 1st and 6th positions, the 2nd and 6th positions, or the 2nd and 7th positions of the naphthalene ring, 2. The compound according to claim 1, wherein All L are alkanediyl groups.
3. The compound according to claim 1, wherein All m are 0.
4. A composition comprising the compound of claim 1.
5. The composition of claim 4, further comprising a polymerization initiator.
6. The composition according to claim 5, wherein The polymerization initiator is a thermal cationic polymerization initiator or a thermal anionic polymerization initiator.
7. The composition of claim 4, further comprising a polymerization inhibitor.
8. A cured product of the compound according to any one of claims 1 to 3 or the composition according to any one of claims 4 to 7.
9. A display device comprising the cured product according to claim 8. 10 . A solid-state imaging device comprising the cured product according to claim 8 .
11. A sealing material comprising the compound according to any one of claims 1 to 3 or the composition according to any one of claims 4 to 7.
12. An insulating material comprising the compound according to any one of claims 1 to 3 or the composition according to any one of claims 4 to 7.
13. The method for producing a compound according to any one of claims 1 to 3, comprising the first step, or the first step and the second step, Step 1: a step of reacting a compound represented by formula (II) with a compound represented by formula (III) to obtain a compound represented by formula (I) wherein A is an O atom; Step 2: a step of obtaining a compound represented by the formula (I) in which A is a S atom by reacting the compound represented by the formula (I) in which A is an O atom with a sulfiding agent, In formula (II), n and R have the same meanings as above, The two -SH groups in formula (II) are bonded to the 1-position and 6-position, 2-position and 6-position, or 2-position and 7-position of the naphthalene ring, In formula (III), R 2 , L and m have the same meanings as above, and X represents a leaving group.
Citation Information
Patent Citations
(METH)acrylate compound and curable composition containing the (METH)acrylate compound
WO2011102258A1